2020
DOI: 10.1016/j.gete.2019.100173
|View full text |Cite
|
Sign up to set email alerts
|

Energy geostructures: A review of analysis approaches, in situ testing and model scale experiments

Abstract: TThis position paper was developed by members of the task force on "Energy Geostructures" of the International Society of Soil Mechanics and Geotechnical Engineering (ISSMGE) Technical Committee TC308 on 'Energy Geotechnics'. The article includes a summary and review of some of the most recent analysis approaches, in situ testing, full scale testing and model scale experiments with a focus on energy piles and other energy geostructures. The geotechnics literature in these topics has increased rapidly in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 172 publications
0
29
0
Order By: Relevance
“…Particularly when considering thermal resistance models, various formulations developed for vertical geothermal borehole heat exchangers are applied to energy piles. However, borehole heat exchanger and energy piles differ in several features, including slenderness ratio, bluffness and heat capacity [e.g., 1,5,9]. Therefore, the available theory for borehole heat exchangers must be applied with caution to energy piles, similar to other formulations available that may apply to relevant energy geostructures.…”
Section: Available Investigation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly when considering thermal resistance models, various formulations developed for vertical geothermal borehole heat exchangers are applied to energy piles. However, borehole heat exchanger and energy piles differ in several features, including slenderness ratio, bluffness and heat capacity [e.g., 1,5,9]. Therefore, the available theory for borehole heat exchangers must be applied with caution to energy piles, similar to other formulations available that may apply to relevant energy geostructures.…”
Section: Available Investigation Methodsmentioning
confidence: 99%
“…This section presents a summary of selected theoretical methods serving the numerical analysis and design of energy geostructures. This summary does not focus on the extensive available numerical studies investigating energy geostructures, which have been discussed elsewhere [1,5,9]. Instead, the following summary is centered on numerical strategies (resorting to the finite element method and included in category 3 approaches) to account for critical features of the heat transfer, mass transfer and deformation phenomena involved with energy geostructures.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the current understanding on the performance of energy geostructures has been provided by Soga and Rui [5] and by Loveridge et al [19]. It is suggested that more work is required to build confidence in the use of such substructure heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal response tests (TRTs) are used to estimate the thermal properties of the energy pile and surrounding subsurface and are commonly performed on vertically-oriented geothermal heat exchangers that can be approximated using a line source [6]. TRTs also provide a means of assessing the soil-structure interaction mechanisms for a given soil deposit.…”
Section: Introduction/backgroundmentioning
confidence: 99%